Reduced bioavailability of cyclosporine A in rats by mung bean seed coat extract - Xiping Li; Ping Gao; Chengliang Zhang; Tao Wu; Yanjiao Xu; Dong Liu (Universidade de São Paulo, 2014)
Mung bean seed coat (MBSC) is a healthcare product in Asian countries. The aim of this study was to investigate the effect of an MBSC ethanol extract on the bioavailability of cyclosporine A (CsA) in rats. Rats were orally dosed with CsA alone or in combination with MBSC ethanol extracts (500 mg/kg, p.o.). The blood levels of CsA were assayed by liquid chromatography with an electrospray ionization source and tandem mass spectrometry (LC-MS/MS). The everted rat intestinal sac technique was used to determine the influence of MBSC on the absorption of CsA. The results reveal that combined CsA intake with MBSC decreased the Cmax, AUC0-t, t1/2z and MRT0-t values of CsA by 24.96%, 47.28%, 34.73% and 23.58%, respectively (P<0.05), and significantly raised the CL/F by 51.97% (P<0.01). The in vitro results demonstrated that significantly less CsA was absorbed (P<0.05). The overall results indicate that after being concomitantly ingested, MBSC reduced the bioavailability of CsA, at least partially, in the absorption phase.